已知Y+2X=1,求代数式(Y+1)^-(Y^-4X)的值.
2个回答
(Y+1)^-(Y^-4X)
=y*y+2y+1-y*y+4x
=2y+4x+1
=2(y+2x)+1
把y+2x=1代入,得:2*1+1=3
所以原代数式的值为3.
相关问题
求代数式的值已知x=1/3,y=1/4,求代数式x-(x+y)+(x+2y)+……(x+103y)的值
已知y+2x=1,求代数式(y+1)^2-(y^2-4x)的值,
已知y+2x=1,求代数式(y+1)2-(y2-4x)的值.
已知y+2x=1,求代数式(y^2+2y+1)-(y^2-4x)的值
已知1/x-1/2y=1/3求代数式2x+3y-4y/x-3y-2y的值
已知2x+y=4,求代数式[(x+y)2-(x-y)2-2y(x-[1/2]y)]÷4y的值.
已知2x+y=4,求代数式[(x+y)2-(x-y)2-2y(x-[1/2]y)]÷4y的值.
已知X=1/3,y=1/4,求代数式x-(x+y)+(x+2y)-(x+3y)+.-(x+103y)的值
已知x=1/3,y=1/4.,求代数式x-(x+y)+(x+2y)-(x+3y)+···-(x+103y)的值
已知x²-4x-1=0求代数式(2x-3)²-(x+y)(x-y)-y²的值